2020
DOI: 10.1111/petr.13682
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric heart‐lung transplantation: A contemporary analysis of outcomes

Abstract: Background Pediatric heart‐lung transplantation (HLT) is rare, and no report has analyzed patient outcomes since time of listing. We analyzed pediatric HLTs to understand risk factors for waitlist and post‐HLT mortality. Methods All pediatric (<18 year old) HLT candidates were identified within the UNOS database (n = 573) and grouped by age, era, and by diagnosis. Logistical regression and Cox proportional hazard modeling identified risk factors for 6‐month WL and overall post‐transplant mortality. Results 209… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The majority of physician respondents reported using pulmonary vasodilators for some children with heart failure and elevated PVR, with that number increasing in the presence of an LVAD. Interestingly, there was a low percentage of respondents recommending listing for combined heart–lung transplant in all three survey case scenarios, reflecting a generalized sense that VAD support is preferable given its overall improved survival 15 …”
Section: Discussionmentioning
confidence: 96%
“…The majority of physician respondents reported using pulmonary vasodilators for some children with heart failure and elevated PVR, with that number increasing in the presence of an LVAD. Interestingly, there was a low percentage of respondents recommending listing for combined heart–lung transplant in all three survey case scenarios, reflecting a generalized sense that VAD support is preferable given its overall improved survival 15 …”
Section: Discussionmentioning
confidence: 96%
“…16 In a recent analysis by Riggs et al, nearly 600 pediatric patients have been listed for heart-lung transplant in UNOS since 1985. 17…”
Section: He Art-lung Alloc Ation P Olicie Smentioning
confidence: 99%
“…Overall, worldwide pediatric heart–lung survival has improved with a 5‐year survival rate of 49% in the 2000s 16 . In a recent analysis by Riggs et al, nearly 600 pediatric patients have been listed for heart–lung transplant in UNOS since 1985 17 . Primary diagnoses for pediatric heart–lung candidates include pulmonary hypertension, congenital heart disease without Eisenmenger syndrome, congenital heart disease with Eisenmenger syndrome, and re‐transplantation.…”
Section: Heart–lung Allocation Policiesmentioning
confidence: 99%
“…For patients on ECMO, waitlist times were shorter, but post‐transplant survival was only 13% after 2 years post‐of transplantation. The authors concluded that with only a small number of HLTs being performed and such guarded survival expectations, other medical therapies might be considered as a bridge to transplant in place of ECMO, such as ventricular assist devices, total artificial hearts, and paracorporeal/intrathoracic artificial lungs 51 …”
Section: Mortalitymentioning
confidence: 99%
“…The authors concluded that with only a small number of HLTs being performed and such guarded survival expectations, other medical therapies might be considered as a bridge to transplant in place of ECMO, such as ventricular assist devices, total artificial hearts, and paracorporeal/intrathoracic artificial lungs. 51 When to discontinue the bridging strategy is not well established. Lancaster et al 3 have described that the median duration of ECMO support in adult series is about 10-18 days, much shorter than the average pediatric waitlist time.…”
Section: Mortalit Ymentioning
confidence: 99%